CORRELATION OF PROSTATIC VOLUME MEASUREMENT BETWEEN TRANSABDOMINAL ULTRASOUND AND CT SCAN - Sujana, Biddulth; Mulyadi, Rahmad; Birowo, Ponco; Prihartono, Joedo (Indonesian Urological Association, 2015)
Objective: This study aims to determine correlation between measurement of prostatic volume and dimensions using transabdominal ultrasound (TAUS) and Computed Tomographic scan (CT scan) in male population ages 50 years and above. Material & method: Research was conducted at Radiology Department, Cipto Mangunkusumo Hospital, Jakarta. Twenty two patients who underwent whole abdominal CT from Desember 2013 to January 2014, were enrolled and examined using TAUS. Results: The calculation shows there is strong correlation between volume measurement, width, and height dimensions between TAUS and CT scan, where the Spearman correlation indicates r = 0.80 with p = 0.000 for volume measurement and r = 0.81 with p = 0.000 for width dimension and r = 0.64 with p = 0.001 for height dimension. There are also regression formula for estimating volume and dimensions measurements using TAUS. Conclusion: This study show strong correlation between volume and dimensions measurement using TAUS and CT scan.